Removal of sulfate pollutant from different samples of a river water using nanozeolite technology, case study: Gamasiab River, Iran - Amin Rezaei; Hossein Babazadeh; Amir Khosrojerdi; Mahdi Sarai-Tabrizi (PLoS ONE, 2025)
Human activities significantly impact on river water quality as a crucial water source. A study in the Gamasiab River analyzed samples from 16 points at three time periods, assessing element concentrations. The most polluted station was identified using spectrophotometric testing and treated with natural and modified zeolite nanoparticles for purification. Various acid and base combinations modified the nanoparticles, optimizing their effectiveness as adsorbents through tests under different conditions. Utilizing the Design Expert model, theoretical adsorption values were determined based on pH and adsorbent-pollutant ratio. The modified samples demonstrated 77% efficiency with 0.2 molar nitric and sulfuric acid. Interaction studies showed how phosphate and nitrate ions affected sulfate adsorption. Optimal adsorption conditions were defined at pH = 9.6 and D/C = 17.01, achieving 86.5% pollutant adsorption. The Freundlich isotherm, with a coefficient of determination of 0.92, was chosen over the Langmuir isotherm (0.79) for its superior performance. Therefore, applying zeolite nanoparticles efficiently eliminated sulfate pollutants from surface water resources at the laboratory.